Assessment of Impact of Aerodynamic Loads on the Stability and Control of the Gyrocopter Model - Tomasz Lusiak; Andrej Novak; Martin Bugaj; Radovan Madlenak (Communications - Scientific letters of the University of Zilina, 2020)
Aerodynamic modelling currently relates to development of mathematical models to describe the aerodynamic forces and moments acting on the aircraft. It is a challenging part of aerodynamics that defines a comprehensive approach to using traditional methods and modern techniques to obtain relevant data. The most complicated task for the aerodynamics and flight dynamics is definition, computation and quantification of the aerodynamic description of an object. This paper presents how to determine the aerodynamic load on a gyrocopter and defines the effect on its stability and control. The first step to solution is to develop simpler approximate aerodynamic model - a model that can be used in analysis of aerodynamic load and can represent the aerodynamic properties of the gyrocopter with an acceptable degree of accuracy. Control and stability are very important parts of aircraft characteristics and therefore those characteristics were analyzed in simulation. Finally, the aerodynamic data outputs are assessed in terms of impact of aerodynamic loads on stability and control of the gyrocopter model.